Regulation of Mitophagy by Sirtuin Family Proteins: A Vital Role in Aging and Age-Related Diseases - Wan, Wei; Hua, Fuzhou; Fang, Pu; Li, Chang; Deng, Fumou; Chen, Shoulin; Ying, Jun; Wang, Xifeng (Frontiers in Aging Neuroscience, 2022)
Sirtuins are protein factors that can delay aging and alleviate age-related diseases through multiple molecular pathways, mainly by promoting DNA damage repair, delaying telomere shortening, and mediating the longevity effect of caloric restriction. In the last decade, sirtuins have also been suggested to exert mitochondrial quality control by mediating mitophagy, which targets damaged mitochondria and delivers them to lysosomes for degradation. This is especially significant for age-related diseases because dysfunctional mitochondria accumulate in aging organisms. Accordingly, it has been suggested that sirtuins and mitophagy have many common and interactive aspects in the aging process. This article reviews the mechanisms and pathways of sirtuin family-mediated mitophagy and further discusses its role in aging and age-related diseases.